Blossom Street : Susannah's Garden - Book 3 - Macomber, Debbie (Don Mills, Ont. : Mira, 2010)
Fifty-year-old Susannah Nelson returns to her childhood home and to the garden she has always loved, where she discovers that some paths were meant to be taken and others were meant to be buried forever.
Keywords: Middle-aged women -- Washington (State); Fiction; Families -- Fiction; Domestic fiction